Eastern features as reflected in the poetry of Hafiz Ibrahim - Al-Nadawi, Meraj Ahmad Meraj (Journal of Humanities & Social Sciences, 2019)
Hafiz Ibrahim, ‘The Nile Poet’ is one of the great literary revival poets in the history of modern Arabic literature. He is the heartbeat of the River Nile. His poetry was characterized by patriotism, charming rhythm and deep impact on recipients. Ibrahim’s poetry teemed with innovative themes and covered all walks of life. He used in his poetry the classical Arabic system of meter and rhyme, but expressed new ideas and feelings, including poetry with political and social commentary. It is in his elegies that Hafiz Ibrahim reached heights not attained by any other poet in modem times. Hafiz is a Nationalist poet who envisioned East in deep sleep and he criticized the Eastern man who is indifferent to events in his country. He invited human to wisdom, contemplation and thought. Hafiz Ibrahim, incompatibility of eastern countries caused their retardation and the unity was a secret of their success. Hafiz Ibrahim established an empire of poetry and built up to the ideals of humanity and national and patriotic purposes, not only in Egypt that go beyond its plans to the East and the world. The aim of this paper is to explore a fairly detailed description of the life of Abraham Hafiz, his poetic journey, poetic intentions and his views and thoughts on eastern people, literature, culture and philosophy.